Neutrophil Count Is Associated With Reduced Gray Matter and Enlarged Ventricles in First-Episode Psychosis. (10th August 2018) - Núñez, Christian; Stephan-Otto, Christian; Usall, Judith; Bioque, Miquel; Lobo, Antonio; González-Pinto, Ana; Pina-Camacho, Laura; Vieta, Eduard; Castro-Fornieles, Josefina; Rodriguez-Jimenez, Roberto; Butjosa, Anna; Janssen, Joost; et al.
Abstract: Although there is recent evidence that cells from the peripheral immune system can gain access to the central nervous system in certain conditions such as multiple sclerosis, their role has not been assessed in psychosis. Here, we aimed to explore whether blood cell count was associated with brain volume and/or clinical symptomatology. A total of 218 participants (137 first-episode psychosis patients [FEP] and 81 healthy controls [HC]) were included in the study. For each participant, a T1 structural image was acquired, from which brain tissue volumes were calculated. We found that, in FEP, neutrophil count was associated with reduced gray matter (GM) volume (β = −0.117, P < .001) and increased cerebrospinal fluid volume (β = 0.191, P = .007). No associations were observed in HC. GM reduction was generalized but more prominent in certain regions, notably the thalamus, the anterior insula, and the left Heschl's gyrus, among many others. Neutrophil count was also associated with the total PANSS score (β = 0.173, P = .038), including those items assessing hallucinations (β = 0.182, P = .028) and avolition (β = 0.197, P = .018). Several confounders, such as antipsychotic medication, body mass index, and smoking, were controlled for. Overall, the present study may represent the first indirect evidence of brain tissue loss associated with neutrophils in psychosis, and lends support to the hypothesis of a dysregulated immune system. Higher neutrophil count was also associated with more severe clinical symptomatology, which renders it a promising indicator of schizophrenia severity and could even give rise to new therapies.